HUBUNGAN ANTARA KADAR AIR TANAH DAN TEKSTUR TANAH TERHADAP LAJU DAN KAPASITAS INFILTRASI DI RUANG TERBUKA HIJAU (RTH) UNIVERSITAS MATARAM - Rahmawati, Yuni; Mahakam Lesmono Aji, Irwan; Sari, Diah Permata (Tengkawang : Jurnal Ilmu Kehutanan, 2024)
The Green Open Space of Mataram University encompasses various types of vegetation, potentially resulting in differences in infiltration rate and capacity within its zones. This study aims to determine the infiltration rate and capacity in the Green Open Space (GOS) of Mataram University and analyze the relationship between soil moisture content and texture with the infiltration rate and capacity in the area. Infiltration measurements were conducted in 10 zones of Mataram University's GOS, with two replications established in each zone: one within tree-covered areas and one in open areas (without tree cover). Laboratory analysis results indicated that the predominant soil texture across all zones of Mataram University's GOS was sandy clay. Soil moisture content in each zone ranged from 1.13% to 9.03%. The highest infiltration rate was found in open zones, with an average value of 48.61 cm/hour across all zones, while the lowest was in closed zones, at 30.58 cm/hour. The highest infiltration capacity was also observed in open zones, with an average value of 25.8 cm/hour, which was higher than that in closed zones (20.4 cm/hour). The t-test results comparing Horton's infiltration rate and capacity with actual infiltration rate and capacity showed no significant difference. Correlation analysis results indicated that soil texture (sand, silt) and soil moisture content were not correlated with infiltration rate and capacity in Mataram University's GOS.Keywords: infiltration, moisture content, GOS, texture.AbstrakRuang Terbuka Hijau Universitas Mataram memiliki berbagai macam jenis vegetasi, sehingga berpotensi dapat memungkinkan terjadinya perbedaan laju dan kapasitas infiltrasi di setiap zona wilayahnya. Penelitian ini bertujuan untuk mengetahui laju dan kapasitas infiltrasi di Ruang Terbuka Hijau (RTH) Universitas Mataram dan menganalisis hubungan antara kadar air dan tekstur tanah di wilayah Ruang Terbuka Hijau (RTH) Universitas Mataram dengan laju dan kapasitas infiltrasi. Pengukuran infiltrasi dilakukan di 10 zona RTH Universitas Mataram, di mana di setiap zona ditetapkan 2 ulangan yaitu 1 ulangan untuk area tertutup dan 1 ulangan pada area terbuka (tanpa tegakan pohon). Hasil laboratorium menunjukkan tekstur tanah yang mendominasi di seluruh zona RTH Universitas Mataram yaitu pasir berlempung. Dan kadar air tanah di setiap zona wilayah RTH Universitas Mataram yaitu berkisar antara 1,13 % - 9,03 %. Laju infiltrasi tertinggi terdapat pada zona terbuka, dengan nilai rata-ratanya untuk semua zona yaitu 48,61 cm/jam dan terendah pada zona tertutup yaitu 30,58 cm/jam. Kapasitas infiltrasi tertinggi terdapat pada zona terbuka, dengan nilai rata-ratanya untuk semua zona terbuka yaitu 25,8 cm/jam lebih tinggi dibandingkan pada zona tertutup yaitu 20,4 cm/jam. Hasil uji-t antara laju kapasitas infiltrasi horton dengan laju kapasitas infiltrasi aktual menunjukkan tidak terdapat perbedaan signifikan. Hasil uji korelasi menunjukkan tekstur tanah (pasir, debu), dan kadar air tanah tidak berkorelasi dengan laju dan kapasitas infiltrasi di RTH Universitas Mataram.Kata kunci: infiltrasi, kadar air, RTH, tekstur.